The Shared Neuroanatomy and Neurobiology of Comorbid Chronic Pain and PTSD. Issue 4 (April 2015) - Scioli-Salter, Erica R.; Forman, Daniel E.; Otis, John D.; Gregor, Kristin; Valovski, Ivan; Rasmusson, Ann M.
<x xml:space="preserve">Abstract</x> Chronic pain and posttraumatic stress disorder (PTSD) are disabling conditions that affect biological, psychological, and social domains of functioning. Clinical research demonstrates that patients who are affected by chronic pain and PTSD in combination experience greater pain, affective distress, and disability than patients with either condition alone. Additional research is needed to delineate the interrelated pathophysiology of chronic pain and PTSD, with the goal of facilitating more effective therapies to treat both conditions more effectively; current treatment strategies for chronic pain associated with PTSD have limited efficacy and place a heavy burden on patients, who must visit various specialists to manage these conditions separately. This article focuses on neurobiological factors that may contribute to the coprevalence and synergistic interactions of chronic pain and PTSD. First, we outline how circuits that mediate emotional distress and physiological threat, including pain, converge. Secondly, we discuss specific neurobiological mediators and modulators of these circuits that may contribute to chronic pain and PTSD symptoms. For example, neuropeptide Y, and the neuroactive steroids allopregnanolone and pregnanolone (together termed ALLO) have antistress and antinociceptive properties. Reduced levels of neuropeptide Y and ALLO have been implicated in the pathophysiology of both chronic pain and PTSD. The potential contribution of opioid and cannabinoid system factors also will be discussed. Finally, we address potential novel methods to restore the normal function of these systems. Such novel perspectives regarding disease and disease management are vital to the pursuit of relief for the many individuals who struggle with these disabling conditions.